Exploring the depths: correlates of depression among seafarers in Mumbai, India - Krishnan, Anusooya; Sumit, Kumar; Chandra, Varalakshmi Chandra (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Seafarers experience unique challenges related to their profession, including risks for mental health. The present study explored the correlates of depression among seafarers in India. Methods. Following ethics clearance, this cross-sectional study was conducted at an international shipping company in Mumbai, India. Using time-bound convenience sampling, 105 multi-state seafarers were recruited following verbal consent. The Beck Depression Inventory and Work-Related Quality of Life scale were used to screen for the study outcomes. Data analysis was performed using Jamovi 2.0. Descriptive statistics and Chi-square tests were used to assess associations, and logistic regression was performed to identify correlates of depression. Results. Of 105 seafarers, the majority (98.1%) were male, most were married (80%), and were aged between 18-35 years (56.2%). About 42.9% had an income of INR 3 lakh (≈$3604) and above monthly. An overwhelming majority had mild mood disturbances, which was found among 90.5% and 8.6% reported depression. Seafarers who engaged in regular physical activity and had higher monthly incomes had higher Work-Related Quality of Life. A significant association was found between depression and isolation (p=0.031) as well as with Work-Related Quality of Life (p=0.012). On logistic regression, we found that the number of hours of work per day, experiencing isolation and Work-Related Quality of Life, significantly predicted depression. Conclusions. The existing burden and treatment gap for mental health morbidity among seafarers needs to be addressed. To address early indications of mental health conditions among seafarers, implementing mental health screening and offering counseling services on board may be the way forward.